RAW Pemutusan Akses Terhadap Penyelenggara Sistem Elektronik Lingkup Privat yang Tidak Terdaftar dalam Perspektif Hak Asasi Manusia - Achmad, Rinalvin; Istislam, Istislam; Dhia Al Uyun (CV. AFDIFAL MAJU BERKAH, 2024)
The policy of terminating access to Private Scope Electronic System Operators, to several internet platforms including: Paypal, Yahoo, Epic Games, Steam, Dota, Counter Strike, Xandr.com, and Origin, which occurred on July 30, 2022. The government's policy in terminating access to unregistered private scope electronic system operators has resulted in material and immaterial losses to citizens who use the platform of unregistered private scope electronic system operators. This research uses normative legal research method, that using a statutory, conceptual, and cases approach to analyze issues related to the termination of access to unregistered Private Scope PSEs. This research concludes that the government's policy of terminating access to unregistered private electronic system operators is contrary to human rights regulation. These rights include the right to access, communicate and obtain information and the right to an economy for citizens who are harmed by the termination of access to unregistered private scope electronic system operators.